Budget Allocation of Taxes to Territorial Budgets - Pařízková, Ivana (Public Governance, Administration and Finances Law Review, 2020)
The contribution deals with the financing of territorial self-governing units in the Czech Republic. The economic basis of local governance is still the most important and the most complicated issue of local governance. Local governances need economic independence for filling their tasks. The aim of this paper is to describe the importance of budget allocation of taxes (BAT) for municipal and regional budgets in the Czech Republic and, on the basis of description and critical analysis or comparison and synthesis of acquired knowledge, to confirm or disprove the hypothesis that partial amendments to the Act on Budget Allocation of Revenue of Certain Taxes to territorial budgets damage municipalities and regions or, on the contrary, strengthen their permanent financial basis. Description, analysis and synthesis are used as a method for writing this article.